Immunological Study for Patient with Verruca Vulgaris and Verruca Plana Caused by HPV in Hilla/ Iraq - Nisreen Kaddim Radi (Journal of Global Pharma Technology, 2017)
Verruca vulgaris and verruca planathey are benign growth  caused by human papilloma virus.Thirty six sample (biopsy, blood serum) collated from patient infected with Verruca  vulgaris  and Verruca  plana whom visit marjan hospital , twenty  blood sample collected from healthy individual person serve as control group .The diagnosis of infection  and the immunological study were  done by using ELISA test ,IgG to HPV and fasligand level (FASL) at blood serum of patient.The result reveled that: histological study for two types of wart show a distinct feature such as the presence of kilobyte in the tissue infected with hpv. There were a significant Mean Differences of FSAL Concentration by wart’s location at the hand 44.4% with Mean± SD of FASL [78.43± 12.46], presence of previous wart Mean± SD of FASL [84.22± 12.51]    and type of warts such as common wart 47.2% withMean± SD of FASL[87.47±11.84]. There was high significant Mean Difference of FSAL and IgG Concentration between patient and control group, (p value ≤ 0.05 is significant).Keywords:-HPV, FASL, IgG, Verruca vulgarus, Apoptosis, Wart.